Hubungan Status Gizi dan Perkembangan Anak Umur 0-24 Bulan (Baduta) di Kabupaten Karawang - Yeni Iswari; Rohayati Rohayati; Susi Hartati (FORIKES, 2021)
The prevalence of malnutrition and stunting in Indonesia has decreased from the previous period, but has not yet reached the target set according to WHO. Nutritional problems can affect a child's level of development. Nutritional problems and developmental disorders in children 0-2 years can determine the quality of life of children in the future. The purpose of this study was to determine the relationship between nutritional status and development. The study was conducted using a cross sectional design for children aged 0-2 years. The number of respondents was 234 with inclusion criteria for healthy children and having KMS / KIA books. Research locations were in the villages of Sukaluyu and Sri Kamulyan, Karawang Regency. Nutritional status was analyzed using the Z score from WHO and child development using KPSP. Statistical data analysis used descriptive analysis, Chi square test and Spearman-rank test. The results showed that the majority of respondents were male, aged 12-24 months. The nutritional status of the children showed that 5.6% were very thin, 12.8% thin, 71.4% normal and 10.3% obese. The level of child development showed 78.6% conformed, 19.2% doubted and 2.1% disturbed. Disturbed aspects of development include fine motor skills and socialization. The results of the Chi square test showed that there was no significant relationship between nutritional status and child development with p-value 0.335 (α> 0.05). The result of the Spearman rank test with a result of 0.088 means that the better the nutritional status, the more appropriate the child's level of development. Nurses need to provide assistance and education to parents regarding nutritional stimulation and child development. Keywords: children under 2 years; nutrition status; child development ABSTRAK Prevalensi gizi kurang dan stunting di Indonesia mengalami penurunan dari periode sebelumnya, tetapi belum mencapai target yang ditetapkan sesuai WHO. Masalah gizi dapat mempengaruhi tingkat perkembangan anak. Masalah gizi dan gangguan perkembangan pada anak 0-2 tahun dapat menentukan kualitas kehidupan anak di kemudian hari. Tujuan penelitian ini adalah mengetahui hubungan status gizi dengan perkembangan anak. Penelitian dilakukan menggunakan desain cross sectional kepada anak usia 0-2 tahun. Jumlah responden 234 dengan kriteria inklusi anak sehat dan memiliki KMS/ buku KIA. Lokasi penelitian di desa Sukaluyu dan Sri Kamulyan Kabupaten Karawang. Status gizi dianalisis menggunakan Z score dari WHO dan perkembangan menggunakan KPSP. Analisis data secara statistik menggunakan analisis deskriptif, uji Chi square dan rank spearman. Hasil penelitian menunjukkan mayoritas responden laki-laki dengan rentang usia 12-24 bulan. Status gizi anak menunjukkan 5,6% kurus sekali, 12,8% kurus, 71,4% normal dan 10,3% gemuk. Tingkat perkembangan anak menunjukkan 78,6% sesuai, 19,2% meragukan dan 2,1% terganggu. Aspek perkembangan yang terganggu antara lain motorik halus dan sosialisasi. Hasil uji Chi square menunjukkan tidak ada hubungan yang signifikan antara status gizi dan perkembangan anak dengan p-value 0,335 (α > 0,05). Hasil uji rank Spearman dengan hasil 0,088 artinya semakin baik status gizi, tingkat perkembangan anak semakin sesuai usianya. Perawat perlu melakukan pendampingan dan edukasi kepada orang tua terkait stimulasi gizi dan perkembangan anak. Kata kunci: baduta; status gizi; perkembangan anak